Report of the Special-purpose Committee on Virtual Participation in the Nomenclature Section - Landrum, Leslie R. (2021)
The Special-purpose Committee on Virtual Participation in the Nomenclature Section was established by the XIX International Botanical Congress (IBC) in Shenzhen, China in 2017, with the mandate “to investigate the possibility of and mechanisms for virtual participation and voting in the Nomenclature Section of an International Botanical Congress via the internet” and to report to the XX IBC. The wide access to the World Wide Web and availability of software for virtual meetings makes the possibility for virtual (online) attendance and voting at a Nomenclature Section seem attainable and advisable. In order to make informed recommendations, we discussed various aspects of online attendance and voting, such as: who should be able to observe?; what would qualify a person to cast institutional votes and personal votes?; if the accumulation of institutional votes should be allowed by an online voter; registration of online voters; how costs would be covered; and recommendations for online attendees. This report provides a synthesis of our discussions and is necessary for interpreting the proposals of this Special-purpose Committee to change aspects of Div. III (Provisions for governance) of the Code (Landrum & al. in Taxon 70: 1397–1398. 2021). This report and those proposals should be consulted together.